2008
DOI: 10.3201/eid1408.071114
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Literature Review of Role of Noroviruses in Sporadic Gastroenteritis

Abstract: We conducted a systematic review of studies that used reverse transcription-PCR to diagnose norovirus (NoV) infections in patients with mild or moderate (outpatient) and severe (hospitalized) diarrhea. NoVs accounted for 12% (95% confi dence interval [CI] 10%-15%) of severe gastroenteritis cases among children <5 years of age and 12% (95% CI 9%-15%) of mild and moderate diarrhea cases among persons of all ages. Of 19 studies among children <5 years of age, 7 were in developing countries where pooled prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
717
5
10

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 875 publications
(760 citation statements)
references
References 39 publications
28
717
5
10
Order By: Relevance
“…In the population of children studied, norovirus infections were significantly less severe than rotavirus infections. The literature concerning symptom severity in norovirus and rotavirus gastroenteritis is heterogeneous [42]. A number of previous studies found lower levels of disease severity in norovirus than in rotavirus gastroenteritis, and most of these were carried out in developed countries [7,[43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…In the population of children studied, norovirus infections were significantly less severe than rotavirus infections. The literature concerning symptom severity in norovirus and rotavirus gastroenteritis is heterogeneous [42]. A number of previous studies found lower levels of disease severity in norovirus than in rotavirus gastroenteritis, and most of these were carried out in developed countries [7,[43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Norovirus is the most common cause of infectious intestinal disease (IID) in the community in high-income countries (1)(2)(3)(4), and a substantial prevalence of norovirus infection has been reported among IID cases seeking medical care (5). Existing estimates of norovirus-associated IID incidence in the community and among individuals presenting to their general practitioner in England are based on electron microscopy, which has poor diagnostic sensitivity for identifying norovirus-associated IID (6)(7)(8); it is very likely that these estimates underrepresent the burden of norovirus disease.…”
mentioning
confidence: 99%
“…Rotavirus A (RVA), norovirus (NoV) and human astrovirus (HAstV) have been described as the most important agents responsible for sporadic cases and outbreaks of acute gastroenteritis (AGE) worldwide (Patel et al 2008). Previous reports have demonstrated that RVA and NoV are common causes of nosocomial diarrhoea in paediatric populations admitted to hospitals (Tran et al 2010).…”
mentioning
confidence: 99%